Readmissions and Mortality During the First Year After Stroke—Data From a Population-Based Incidence Study - Abreu, Pedro; Magalhães, Rui; Baptista, Diana; Azevedo, Elsa; Silva, Maria Carolina; Correia, Manuel (Frontiers in Neurology, 2020)
Background: After a first-ever-in-a-lifetime stroke (FELS), hospital readmissions are common and associated with increased mortality and morbidity of stroke survivors, thus raising the overall health burden of stroke. Population-based stroke studies on hospital readmissions are scarce despite it being an important healthcare services quality indicator. We evaluated unplanned readmissions or death during the first year after a FELS and their potential predictors, based on a Portuguese community register. Methods: Data were retrieved from a population-based prospective register undertaken in Northern Portugal (ACIN2) in 2009-2011. Retrospective information about unplanned hospital readmissions and case fatality within one year after FELS index hospitalization (FELS-IH) was evaluated. Readmission/death-free survival one year after discharge was estimated using the Kaplan-Meyer method. Independent risk factors for readmission/death were identified using Cox proportional hazard models. Results: Unplanned readmission/death within one year occurred in 120 (31.2%) of the 389 hospitalized FELS survivors. In 31.6% and 33.5% of the cases, it occurred after ischemic stroke or intracerebral haemorrhage, respectively. Infections and cerebrovascular and cardiovascular diseases were the main causes of readmission. Of the readmissions, 65.3% and 52.5% were potentially avoidable or stroke-related, respectively. Male sex, age, previous and post-stroke functional status, and FELS-IH length of stay were independent predictors of readmission/death within one year. Conclusions: Almost one-third of FELS survivors were readmitted/dead one year after their FELS-IH. This outcome persisted after the first months after stroke hospitalization in all stroke subtypes. Timely interventions should be implemented to avoid readmissions and their poor prognosis.